2008
DOI: 10.1186/1471-2164-9-113
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mapping of Brassica juncea and Arabidopsis thaliana using Intron Polymorphism (IP) markers: homoeologous relationships, diversification and evolution of the A, B and C Brassica genomes

Abstract: Background: Extensive mapping efforts are currently underway for the establishment of comparative genomics between the model plant, Arabidopsis thaliana and various Brassica species. Most of these studies have deployed RFLP markers, the use of which is a laborious and time-consuming process. We therefore tested the efficacy of PCR-based Intron Polymorphism (IP) markers to analyze genome-wide synteny between the oilseed crop, Brassica juncea (AABB genome) and A. thaliana and analyzed the arrangement of 24 (prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
219
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(232 citation statements)
references
References 43 publications
(64 reference statements)
9
219
2
2
Order By: Relevance
“…However, the number of identified miRNAs is substantially less compared to the, 199 miRNAs belonging to 121 miRNA families identified in Arabidopsis deposited in the miRNA database (http://www.mirbase.org). Many comparative mapping studies of A. thaliana show the presence of an average of 3 copies of an Arabidopsis chromosome segment in the Brassica genome (Panjabi et al, 2008;Parkin et al, 2005;Teutonica and Osborn, 1994;Truco et al, 1996), although this might not hold true for miRNA genes. Therefore, with the availability of complete genome sequences in the near future, the identification of more members of miRNA belonging to previously identified or new miRNA families is expected.…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of identified miRNAs is substantially less compared to the, 199 miRNAs belonging to 121 miRNA families identified in Arabidopsis deposited in the miRNA database (http://www.mirbase.org). Many comparative mapping studies of A. thaliana show the presence of an average of 3 copies of an Arabidopsis chromosome segment in the Brassica genome (Panjabi et al, 2008;Parkin et al, 2005;Teutonica and Osborn, 1994;Truco et al, 1996), although this might not hold true for miRNA genes. Therefore, with the availability of complete genome sequences in the near future, the identification of more members of miRNA belonging to previously identified or new miRNA families is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Triplication of 24 ancestral GBs theoretically resulted in 72 GBs comprising quasidiploid Brassiceae genomes. Out of the 24 GBs, only 13 (54%) (Parkin et al, 2005;) and 14 (58%) (Panjabi et al, 2008) blocks were found as three or more copies in the rapa (A) genome of B. napus or B. juncea. In the nigra (B) and oleracea (C) genomes, only seven (29%) (Panjabi et al, 2008) and eight (33%) (Kaczmarek et al, 2009) GBs were reported as three or more homoeologous copies in B. juncea and B. oleracea, respectively.…”
Section: Diploidization: Retention Versus Loss Of Genomic Blocksmentioning
confidence: 99%
“…Out of the 24 GBs, only 13 (54%) (Parkin et al, 2005;) and 14 (58%) (Panjabi et al, 2008) blocks were found as three or more copies in the rapa (A) genome of B. napus or B. juncea. In the nigra (B) and oleracea (C) genomes, only seven (29%) (Panjabi et al, 2008) and eight (33%) (Kaczmarek et al, 2009) GBs were reported as three or more homoeologous copies in B. juncea and B. oleracea, respectively. Comparing these data with 83 to 100% of duplicated GBs retained in the Australian species, triplicated Brassiceae genomes show faster diploidization and/or originated earlier (13 to 17 mya suggested by Yang et al, 2006).…”
Section: Diploidization: Retention Versus Loss Of Genomic Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a large number of markers are available for the Brassica genomes (A, B, and C) that have been used in recent years to tag simple Mendelian traits and to map quantitative trait loci (Mahmood et al 2007) and can be used to detect interspecific hybrids and genetic introgression. Panjabi et al (2008) used intron polymorphism (IP) markers to identify a high degree of colinearity between the A and B genomes of Brassica juncea with the A genome of B. napus and the B genome of B. nigra, respectively, which suggested low levels of chromosomal change after polyploidization. Cytological observations in digenomic triploids (BBC and CCB) generated from interspecific hybridization between B. carinata and B. nigra and between B. carinata and B. oleracea indicated that the Brassica B genome chromosomes may not form homeologous pairs with chromosomes of the A and C genomes in interspecific crosses (Meng et al 1998).…”
mentioning
confidence: 99%